2007
DOI: 10.1577/m06-197.1
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Shoreline Seines with Fyke Nets for Sampling Littoral Fish Communities in Floodplain Lakes

Abstract: We compared shoreline seines with fyke nets in terms of their ability to sample fish species in the littoral zone of 22 floodplain lakes of the White River, Arkansas. Lakes ranged in size from less than 0.5 to 51.0 ha. Most contained large amounts of coarse woody debris within the littoral zone, thus making seining in shallow areas difficult. We sampled large lakes (.2 ha) using three fyke nets; small lakes (,2 ha) were sampled using two fyke nets. Fyke nets were set for 24 h. Large lakes were sampled with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
30
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 6 publications
2
30
0
Order By: Relevance
“…These results reinforce the view that using a single gear or sampling a single habitat to describe species prevalence may provide a substantially incomplete or biased assessment (e.g., Weaver et al, 1993;Clark et al, 2007;Trebitz et al, 2009). Although all of the nonnative fishes were captured in at least two gears, excluding shallow habitats would have failed to detect threespine stickleback and greatly underestimated tubenose goby and brook silverside abundance, as well as the spatial extent of the round goby population.…”
Section: Role Of Sampling Gearsupporting
confidence: 71%
See 1 more Smart Citation
“…These results reinforce the view that using a single gear or sampling a single habitat to describe species prevalence may provide a substantially incomplete or biased assessment (e.g., Weaver et al, 1993;Clark et al, 2007;Trebitz et al, 2009). Although all of the nonnative fishes were captured in at least two gears, excluding shallow habitats would have failed to detect threespine stickleback and greatly underestimated tubenose goby and brook silverside abundance, as well as the spatial extent of the round goby population.…”
Section: Role Of Sampling Gearsupporting
confidence: 71%
“…Our trawl was equipped with a fine-mesh liner to increase the catch of small-bodied fishes such as juvenile Eurasian ruffe and, incidentally, juvenile rainbow smelt. Fyke nets target larger, mobile fish (Portt et al, 2006), as well as those with migratory behavior; thus, they generally sample more fish and more species in littoral zones than beach seines (Clark et al, 2007). Common carp, white perch, and tubenose goby were all common in fyke nets, suggesting they undertake inshore-offshore diel movement.…”
Section: Role Of Sampling Gearmentioning
confidence: 99%
“…Furthermore, mini-fyke nets have been compared with other gears for assessing fish community structure. They tended to collect more fish and more species of fish than other gears, including electrofishing, gill nets, and seines (Clark et al 2007;Eggleton et al 2010;Cvetkovic et al 2012). Weaver et al (1993) also found that this gear resulted in better descriptions of littoral fish communities than did gill nets or seines.…”
mentioning
confidence: 96%
“…Furthermore, Wegener rings and block nets typically involve the use of the fish toxicant rotenone, which has been increasingly discouraged due to public concerns (Finlayson et al 2000). Despite the success of seines for sampling in SB habitats, they, too, are ineffective in areas with dense vegetation or structure due to snagging and rolling (Pierce et al 1990;Lapointe et al 2006;Clark et al 2007). Airboat electrofishing has been deemed effective in these habitats, but similar to other electrofishing methods, it is biased toward larger fishes (Chick et al 1999).…”
mentioning
confidence: 99%
See 1 more Smart Citation